Impact of internal audit function (IAF) on financial reporting quality (FRQ): evidence from Saudi Arabia - Al-Shetwi, Mohammed; Ramadilli Mohd, Shamsher Mohamad; Chowdury, Taufiq Hassan Shah; Muhamad Sori, Zulkarnain (Academic Journals, 2011)
This study examined the impact of the quality of the internal audit function (IAF), an integral part of corporate governance structure, on the financial reporting quality (FRQ) of all Saudi companies listed in the Saudi stock exchange (TADAWL) in 2009, excluding banks. Both secondary and primary information was collected through a matched survey and interview of internal and external auditors. The findings show weak association between IAF quality and FRQ. The findings imply that the listed firms merely use IAF to provide a symbolic conformity to capital market authority (CMA) regulations. For better internal control and global recognition, CMA needs to put in place more initiatives to increase the role of IAF on firms in Saudi Arabia. Considering the environmental factors of emerging institutions, this study added different insights on the issue of IAF and its role in FRQ in the oil-based economy of Saudi Arabia.